Mitochondrial Dysfunction in Congenital Heart Disease - Julie Pires Da Silva; Mariana Casa de Vito; Carissa Miyano; Carmen C. Sucharov (Journal of Cardiovascular Development and Disease)
Mitochondria play a crucial role in multiple cellular processes such as energy metabolism, generation of reactive oxygen species, excitation–contraction coupling, cell survival and death. Dysfunction of mitochondria contributes to the development of cancer; neuromuscular, cardiovascular/congenital heart disease; and metabolic diseases, including diabetes. Mitochondrial dysfunction can result in excessive reactive oxygen species, a decrease in energy production, mitophagy and apoptosis. All these processes are known to be dysregulated in cardiovascular diseases. The focus of this review is to summarize our current knowledge of mitochondrial dysfunction, including mitophagy and apoptosis, in pediatric congenital heart disease due to maternal diabetes or due to structural cardiac defects, with a focus on single-ventricle congenital heart disease. We also discuss recent mitochondria-targeted therapies for cardiovascular diseases.